Effects of accommodation and simulated convergence on anterior scleral shape. (3rd June 2020) - Niyazmand, Hamed; Read, Scott A; Atchison, David A; Collins, Michael J
Abstract: Purpose: The sclera plays an important role in the biomechanical stability of the eye. We aimed to examine if changes in the shape of the anterior sclera occur in response to accommodation and convergence. Methods: Thirty‐six healthy young adult participants aged between 18 and 30 years including 18 myopes (–0.5 to –4.0 D) and 18 emmetropes (+0.5 to –0.25 D) were recruited. Eye surface profilometry was used to evaluate the anterior eye surface shape before and during visual tasks involving accommodation (5.0 D demand), simulated convergence (9° demand) and their combination. The changes in the sagittal height and axial radius of curvature of the nasal ( n  = 25) and temporal ( n  = 31) corneal periphery and anterior sclera were analysed in those participants with complete and reliable data on these sides. Results: Significant changes were confined to the nasal anterior scleral surface. A significant forward movement of the surface accompanied accommodation (mean change: 5 ± 2 µm), convergence (19 ± 6 µm), and their combination (16 ± 6 µm). There was flattening with convergence (0.092 ± 0.044 mm) and with the combination of accommodation and convergence (0.201 ± 0.071 mm). The changes in response to accommodation and convergence increased peripherally. Changes were not significantly different between low to moderate myopes and emmetropes. Conclusions: Accommodation and simulated convergence affect the nasal anterior scleral shape, with the greatest changes associated with convergence and being most evident in the more peripheral nasal scleral regions.